Teachers’ attitudes towards code-switching in the English as a foreign language classroom - Engku Ibrahim, Engku Haliza (2010)
Code-switching has always been an intriguing phenomena to sociolinguists. While the general attitude to it seems negative, people seem to code-switch quite frequently. Teachers of English as a foreign language too frequently claim that they do not like to code-switch in the language classroom for various reasons – many are of the opinion that only the target language should be used in the classroom. This study looks at the teachers’ attitudes towards code-switching in teaching English as a foreign language to Malay students at one of the local universities in Malaysia. Data was collected through observations, questionnaires and interviews. Each subject was observed, their language use were recorded, transcribed and then analyzed using the functions proposed by Gumperz (1982). This study provides a qualitative analysis of the linguistic features of code-switching and the reasons for its occurrence The results of the study showed that teachers do code-switch in the language classroom, despite their claim they do not. Each subject performed different functions of code-switching. Altogether, there were seven functions of code-switching used in the classroom by the subjects of this study. The functions were: message reiteration, message qualification, interjection or sentence filler, personalization versus objectivization, quotation, specific features of Islamic English, and the transfer of subconscious markers. Analysis of the data shows that, in most cases, code switching by teachers serves pedagogical purposes.